МӘМЛЕКЕТИМИЗДЕ МАКРО ЭКОНОМИКАЛЫҚ ТУРАҚЛЫЛЫҚ ҲӘМ ИННОВАЦИЯЛЫҚ ӨСИЎ ТЕНДЕНЦИЯЛАРЫ - Хожалепесов, П.З.; Зинатдинов, Б.П. (FAN va JAMIYAT, 2019)
The article is devoted to the issues of the main directions of the socio-economic development of the Republic of Uzbekistan.